Prognostic implications of myocardial creatine kinase and cardiac troponin in coronary artery bypass surgery - Taniguchi,Fábio P. (2003)
OBJECTIVES: To evaluate the prognostic implications of myocardial creatine kinase and troponin I (cTn I) in blood samples from the coronary sinus of patients submitted to coronary artery bypass surgery both with and without ischemic preconditioning. METHODS: From October 1998 to May 1999, 35 patients with coronary artery disease who were submitted to coronary artery bypass surgery were studied. Samples containing creatine kinase and cTn I were obtained from the great cardiac vein during surgery at the onset of cardiopulmonary bypass, at the end of the first anastomosis, and at the end of cardiopulmonary bypass. In May 2002, 29 patients were evaluated in regards to the angina functional class, congestive heart failure, number of hospitalizations, myocardial infarction and death. There were 15 patients in the Preconditioned group and 14 in the Control group. Each group was subdivided into patients with and without cardiovascular symptoms. RESULTS: The Control and Preconditioned groups were not significantly different in relation to frequency of cardiovascular symptoms. There were progressive increases of the creatine kinase and cTn I levels at different Interval s of the study. The cTn I in the Preconditioned group was 1.21 ± 0.64 ng/mL and 3.19 ± 3.21 ng/mL in the Control group (p<0.05). The Control group with symptoms had the highest level for cTn I of 5.07 ± 3.69 ng/mL, significantly higher than all other groups (p<0.05). CONCLUSIONS: The Preconditioned group had the lowest level of cTn I. The cTn I may be a marker for late evolution in patients submitted to coronary artery bypass surgery.